How effective are community pedestrian safety training workshops? Short-term findings from a program in California. (March 2019) - Barajas, Jesus M.; Beck, Kate M.; Cooper, Jill F.; Lopez, Ana; Reynosa, Amanda
Abstract: Introduction: Pedestrians and bicyclists make up a disproportionate share of road deaths and injuries, and low-income, majority person-of-color communities tend to face the greatest danger. Comprehensive pedestrian safety programs targeted toward such communities have the potential to build communities' capacity to address safety issues, but there is a lack of systematic research and evaluation on how effective these programs are. Methods: We use a mixed-methods approach of surveys, participant observation, and follow-up interviews to evaluate a community-based pedestrian and bicycle safety program in 13 California communities for its short-term effectiveness in meeting five goals: providing relevant safety information to participants, building community partnerships, increasing walking and cycling in host communities, improving perceptions of pedestrian and bicyclist safety, and planning for additional safety countermeasures. Results: Workshops have beneficial effects on identifying community needs, developing partnerships between stakeholders, and changing perceptions of safety in historically disadvantaged communities. The program improves participants' perceptions of the role that community organizations and community events play in pedestrian safety efforts. The program also provides a critical space for community stakeholders to meet, learn a common language about safety, and develop partnerships around pedestrian and bicycle safety. Host communities have used the workshops as support for grant applications, and several have obtained funding for pedestrian and bicycle improvements. Conclusion: The workshops intervene in the short-term on multiple levels to improve pedestrian safety as described in program goals. This study provides a model for evaluating a program for its short-term effects, providing a baseline set of conditions for longer-term evaluation. Highlights: Workshops build community capacity for pedestrian safety planning Social elements of workshop activities shifted participant's safety perceptions Continuing evaluations are necessary to measure longer-term safety outcomes Evaluations must be flexible to assess changing goals in established programs